2012
DOI: 10.1021/ic3012712
|View full text |Cite
|
Sign up to set email alerts
|

Fe(II) Complexes That Mimic the Active Site Structure of Acetylacetone Dioxygenase: O2 and NO Reactivity

Abstract: Acetylacetone dioxygenase (Dke1) is a bacterial enzyme that catalyzes the dioxygen-dependent degradation of β-dicarbonyl compounds. The Dke1 active site contains a nonheme monoiron(II) center facially ligated by three histidine residues (the 3His triad); coordination of the substrate in a bidentate manner provides a five-coordinate site for O2 binding. Recently, we published the synthesis and characterization of a series of ferrous β-diketonato complexes that faithfully mimic the enzyme-substrate intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 61 publications
3
28
0
1
Order By: Relevance
“…A similar intermediate was proposed in studies of an Fe(II)-acetylacetone model of β-diketone dioxygenase [190]. Indirect evidence for the intermediacy of an iron(II)-superoxo complex was also cited in studies of 52 ( Figure 27), which reacted with O 2 only in the presence of reductant and proton donors [191] or substrates with weak C-H bonds [192] to yield iron(III)-hydroperoxo or iron(IV)-oxo species.…”
Section: Monoiron Superoxo and Hydroperoxo Complexessupporting
confidence: 58%
“…A similar intermediate was proposed in studies of an Fe(II)-acetylacetone model of β-diketone dioxygenase [190]. Indirect evidence for the intermediacy of an iron(II)-superoxo complex was also cited in studies of 52 ( Figure 27), which reacted with O 2 only in the presence of reductant and proton donors [191] or substrates with weak C-H bonds [192] to yield iron(III)-hydroperoxo or iron(IV)-oxo species.…”
Section: Monoiron Superoxo and Hydroperoxo Complexessupporting
confidence: 58%
“…2829 The formation of a dimeric peroxo-bridged structure from the reaction of monomeric Fe II complex + O 2 was demonstrated in a separate study utilizing hydrotris-(pyrazol-1-yl)borate-bound iron(II)–diketonate complex. 97 …”
Section: Dioxygen Activation By Nonheme Iron Complexesmentioning
confidence: 99%
“…Within the Tp Ph2 Fe-(acac X ) series, it thus appeared that O 2 reactivity was primarily governed by the relative energies of acac x π-electrons, not the Fe redox potentials. 37 Concluding, it was confirmed that only activated, electronrich substrate ligands (malonates) can be cleaved in model systems for the Dke1 in the absence of supporting secondary interactions. 4.…”
Section: B Model Systemsmentioning
confidence: 80%
“…37 When the reactions were carried out in acetonitrile as the solvent (with trace amounts of water), some [Tp Me2 Fe(acac x )] complexes finally yielded in trinuclear compounds with bridging carboxylate, oxido, and hydroxido ligands, related to 16. 33 Unlike the [Tp Me2 Fe(acac x )] series, complexes with Tp Ph2 or TlP ligands exhibited a significantly lower reactivity upon exposure to O 2 .…”
Section: B Model Systemsmentioning
confidence: 99%